RESPONS PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) TERHADAPPEMBERIANPUPUK KANDANG KELINCI DAN PUPUK NPK (16:16:16) - Hendrikson Ferrianto Sitompul; Toga Simanungkalit; Lisa Lisa Mawarni (Jurnal Agroekoteknologi, 2014)
One of the factors that determine the quality of cocoa seedlings are growing medium that has achemical and physical fertility, in order to obtain a good and healthy seeds for furthergrowth.Growing media fertility can be improved or enhanced with inorganic or organic fertilizer,such as Rabbit manure, which is one type of solid waste rabbit manure and NPK fertilizer, isexpected to increase the growth of cocoa seedling. This research had been conducted atexperimental field of Fakultas Pertanian USU in July 2013 until September 2013, using factorialrandomized block design with two factor, i.e. dose of rabbit manure (0, 50, 100, and 150 gram perpolybag) and dose of NPK fertilizer (0 ,4, 8, and 12 gram per polybag). Parameter observed wereplant height, stem diameter, number of leaf, summarize of leaf area, fresh weight of shoot, freshweight of root, dry weight ofshoot and dry weight of root. The result showed response of rabbitmanure on cocoa seed significantlyincrease plant height, total of leaf area, and dry shoot weight.The best results from this experimental were obtained in the treatment of rabbit manure at 150g/polybag.________________________________________________________________________________Keywords: Rabbit manure, NPK Fertilizer, Cocoa Seedling